Gaining Instead of Losing: The Image of Dunhuang as a Religious Heritage in a WeChat Mini-Programme - Song, Zhuyun (Religions, 2023)
In 2020, a WeChat mini-programme called the Dunhuang E-Tour (云游敦煌) was launched during the COVID-19 pandemic to showcase one of China’s most important religious heritage sites, the Dunhuang Mogao Grottoes (also known as the Dunhuang Caves), and it attracted a considerable number of online tourists. Unlike the colonial image of Dunhuang in Chinese public discourse, the mini-programme does not focus on Dunhuang’s history; rather, it provides a dynamic and interactive representation of Dunhuang’s religious murals, painted sculptures and cave architecture. To reflect the impact of the mini-programme’s digital mechanisms on users’ experience, this study adopts an analytical framework that combines the walkthrough method and religious tourist perspectives to explore the image of the digital Dunhuang and how it was shaped. The analysis finds that the functions of the Dunhuang E-Tour create a culturally rich image of Dunhuang, which subverts its decades-long Dunhuang image as a site of loss in Chinese public discourse. This difference in images mirrors the potential impact of China’s recent cultural policy of ‘cultural confidence’ in relation to its cultural and creative industries.